2004
DOI: 10.1038/sj.bjc.6601758
|View full text |Cite
|
Sign up to set email alerts
|

Small-cell carcinoma of the gastrointestinal tract: a retrospective study of 64 cases

Abstract: Small-cell carcinoma (SmCC) of the gastrointestinal tract is a very rare and aggressive malignancy. To better define its clinicopathological features, the records of all patients with this disease seen at Memorial Sloan Kettering Cancer Center between 1980 and 2002 (n ¼ 64) were reviewed. The most common primary tumour locations were in the large bowel and oesophagus. Predisposing medical conditions for non-small-cell cancers, positive family cancer history, and metachronous tumours were common. In all, 37% ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
104
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(111 citation statements)
references
References 42 publications
4
104
2
1
Order By: Relevance
“…The objective response rate to platinum-based chemotherapy was 77.8% for the patients with SCLC, and the MST in the present study was 13.6 months, which was similar to previously reported survival times [33,34,36]. On the other hand, the efficacy of such regimens against EP-NECs seemed to be worse in the present study, with a response rate of 31.7% compared with 33–66.7% in previous reports [5,7,10,20,21]. Although the reason for the difference in the treatment efficacies was unknown, possible reasons include the differences in the criteria used to evaluate response and the relatively small number of patients.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The objective response rate to platinum-based chemotherapy was 77.8% for the patients with SCLC, and the MST in the present study was 13.6 months, which was similar to previously reported survival times [33,34,36]. On the other hand, the efficacy of such regimens against EP-NECs seemed to be worse in the present study, with a response rate of 31.7% compared with 33–66.7% in previous reports [5,7,10,20,21]. Although the reason for the difference in the treatment efficacies was unknown, possible reasons include the differences in the criteria used to evaluate response and the relatively small number of patients.…”
Section: Discussionsupporting
confidence: 77%
“…Additionally, the response rates of EP-NECs with different primary sites were significantly different, with the HBP group showing the lowest response rate. This finding also disagreed with Brenner et al’s [5 ]report, which showed no differences in the response to chemotherapy among the different anatomical locations. The patients with EP-NECs tended to have unfavorable outcomes compared with the patients with SCLC in our study.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Diagnoses were confirmed immunohistochemically, using antibodies to chromogranin A, synaptophysin and neuron specific enolase (NSE). Mixed SCC was defined as tumors containing both SCC and non-SCC components, regardless of the proportion of the latter [12].…”
Section: Methodsmentioning
confidence: 99%
“…The most common type is medullary, followed by mushroom, and ulcerative. 17 These tumors can be divided into different subtypes according to their histopathological and morphological characteristics and degree of differentiation. The majority are NECs and MANECs.…”
Section: Pathologymentioning
confidence: 99%